DAMPAK ADANYA TIKTOK SHOP TERHADAP PERKEMBANGAN PENJUALAN USAHA MIKRO KECIL DAN MENENGAH LOKAL INDONESIA - Manullang, Richard Barton; Pratama, Arya Satya; Wicaksono, M. Dwi Ananda (Investama : Jurnal Ekonomi dan Bisnis, 2024)
UMKM stands for Small and Medium Micro Enterprises. UMKMs are productive economic enterprises run by individuals or small business entities, so UMKMs can be summed up as economic enterprises carried out by lower middle society. Tiktok shop is a social commerce feature that involves marketing and selling products through the Tiktok platform. This study uses qualitative descriptive methods using primary and secondary data sources. The main data collection techniques are used through interviews. This method is used to understand and explain the increase in sales in the clothing industry through the Tiktok store platform. It has 2 hypotheses namely hypothesis X1 and Hypothesis X2, where hypothesis X1 is: The existence of Tiktok shop can increase the sales of local UMKMs and the economy of the UMKMs. Then for Hypothesis X2 it is: The existence of Tiktok shop does not have a big impact on the sales and economy of local UMKMs. The conclusions of the research show that Tiktokshop increases the revenue of the clothing industry because it is a highly effective product promotion tool and has billions of users worldwide. This is a great opportunity to make the product famous all over the world.